An unusual case of gastrointestinal fungal infection mimicking colon cancer: a case report - Azmi, Arif Jamal Bin; Rahman, Mohd Nor Bin Gohar; Omar, Siti Zarqah Binti; Rahim, Mohd Fadliyazid Bin A. B. (International Surgery Journal, 2022)
Fungal gastrointestinal infection causing bowel obstruction mimicking the presentation of colon carcinoma is rare. We reported a case of gastrointestinal fungal infection in an immune-competent individual who presented with acute colonic obstruction. He was successfully treated with combination of surgical intervention and antifungal regimes.